If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (64x + 75y) + -1(-32x + 7y) = 0 Remove parenthesis around (64x + 75y) 64x + 75y + -1(-32x + 7y) = 0 64x + 75y + (-32x * -1 + 7y * -1) = 0 64x + 75y + (32x + -7y) = 0 Reorder the terms: 64x + 32x + 75y + -7y = 0 Combine like terms: 64x + 32x = 96x 96x + 75y + -7y = 0 Combine like terms: 75y + -7y = 68y 96x + 68y = 0 Solving 96x + 68y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-68y' to each side of the equation. 96x + 68y + -68y = 0 + -68y Combine like terms: 68y + -68y = 0 96x + 0 = 0 + -68y 96x = 0 + -68y Remove the zero: 96x = -68y Divide each side by '96'. x = -0.7083333333y Simplifying x = -0.7083333333y
| tn=5+(n-1)3 | | 1/4-x=1/2x+9/4 | | (56x+46y)-(2x-7y)= | | y=-x^2+4x+6 | | (54x+63y)-(-31x+4y)= | | 2p+k=4 | | 6x-11y=10 | | 130=2x+6(2x-4) | | (78x-67y)-(49x+33y)= | | 3m+6m+7m-9= | | P-2k=7 | | 3/5x-1/5x=-3 | | n-5/7=4 | | 7(4)+4y=56 | | 7x+4(0)=56 | | 2y-3x=50 | | 16x^2-72x=15 | | 7(0)+4y=56 | | 1-(8)/(x+1)^3=0 | | (4x+2)/5*9=-18 | | 3a+20-a+10=180 | | 3[6s+12]-[10s-6]=0 | | 0.5n=0.35 | | 12x+4-8=2x-22 | | ((3^3-10)+(-7))/((-5)^2+(-4x-5)) | | 52=2x+4(x+4) | | 5+4e^2x=20 | | (65x+63y)-(26x-4y)= | | (60x+63y)-(-43x+13y)= | | x^3-3x^2+3x+6=0 | | 9(2x-6)=3(6x+9) | | 9(y-2)+5(6y-18)-13y=-4 |